High Voltage Insulation Surface Condition Analysis Using Time Frequency Distribution - Norddin, Nurbahirah; Abdullah, Abdul Rahim; Zainal Abidin, Nur Qamarina; Aman, Aminudin (AENSI, 2013)
This paper presents an analysis of high voltage insulation surface condition under high contamination level using experimental test of tracking and erosion according to BS EN 60587 standard. Surface condition on glass and polymeric types of insulation is investigated. The leakage current patterns on these types of insulation are applied for surface condition classification. Due to the limitation fast Fourier transforms (FFT), a new approach of time frequency distributions (TFD) analysis is employed. Spectrogram and s-transform as time frequency distribution (TFD) are then applied to represent and analysis of the leakage current (LC) in time frequency representation (TFR) in temporal and spectral. These techniques extract relevant information from leakage current (LC) signal, and then leakage current (LC) parameters are estimated to identify its characteristics. These include root mean square current (RMS), total harmonic distortion (THD), total non harmonic distortion (TnHD) and total current waveform distortion (TWD). Leakage current’s instantaneous root mean square current per unit value and total current waveform distortion percentage are useful to reveal the insulator surface condition. Referring to rules based value, the classification of material surface state could be determined instantaneously. Instead of fast Fourier transform (FFT), it was found that time frequency distribution (TFD) is an appropriate tool for surface condition classification. Then, the unsymmetrical discharge pattern on polymeric insulation material indicated that erosion is occurred on the surface of the insulator.